Integrating Good Governance Business Sharia into Maqasid Sharia: Evidence from Islamic Rural Banks in Indonesia - Muhammad Ridlo Zarkasyi; Agung Lia Handayani; Setiawan bin Lahuri; Royyan Ramdhani Djayusman; Adi Rahmannur Ibnu (Islamiconomic : Jurnal Ekonomi Islam, 2025)
This study explores the implementation of Good Governance Business Sharia (GGBS) at PT BPRS Mitra Mentari Sejahtera through the framework of Maqasid Shariah. The research examines how governance principles rooted in Sharia values are translated into institutional practices and how they contribute to the realization of ethical and sustainable business objectives. Using a descriptive qualitative approach with a case study design, data were collected through interviews, documentation, and institutional reports, then analyzed using Atlas.ti 09. Findings reveal that BPRS Mitra Mentari Sejahtera has effectively incorporated GGBS principles by promoting transparency, accountability, and adherence to Sharia ethics. However, limited public disclosure—particularly the unavailability of annual reports—remains a major challenge, potentially weakening stakeholder trust and institutional credibility. The study emphasizes the need for stronger transparency mechanisms, enhanced collaboration with Sharia supervisory bodies, and continuous education to reinforce Maqasid Shariah within governance structures. Overall, this research underscores the pivotal role of GGBS in achieving Sharia objectives and advancing ethical governance in the Islamic financial sector.